Degenerative Changes of the Facet Joints in Adults With Lumbar Spondylolysis - Goda, Yuichiro; Sakai, Toshinori; Harada, Taihei; Takao, Shoichiro; Takata, Yoichiro; Higashino, Kosaku; Harada, Masafumi; Sairyo, Koichi (Clinical spine surgery, 2017)
Radiologic analysis using computed tomography. To analyze the degenerative changes of the facet joints in patients with spondylolysis in comparison with control subjects. Defects of the pars interarticularis are thought to result in a reduction of biomechanical stress on adjacent facet joints. Therefore, degenerative changes of the facet joints in patients with spondylolysis are expected to be less than those in patients without spondylolysis. Abdominal and pelvic multidetector computed tomography scans of 2000 subjects, performed for conditions unrelated to low back pain, were reviewed. A total of 107 patients (37 women and 70 men) with L5 spondylolysis were identified [spondylolysis (+) group]. Sex-matched and age-matched controls without spondylolysis were chosen randomly [spondylolysis (-) group]. Subjects in the spondylolysis group were subdivided into either bilateral spondylolysis or unilateral spondylolysis groups for comparison with the control group. Four radiologic findings (narrowing, sclerosis, osteophyte, and bone cyst) indicative of degenerative change of the facet joints adjacent to the L5 pars defects were evaluated and the degree of degenerative change was graded by summing the number of degenerative changes (score range, 0-4). The χ test and Mann-Whitney U test were used for statistical analysis. Significantly more degenerative changes in both L4/L5 and L5/S facet joints were found in the spondylolysis (+) group than in the spondylolysis (-) group (χ test, P <0.05). Degenerative changes of the facet joints at both L4/L5 and L5/S were more severe in the bilateral spondylolysis (+) group than in the spondylolysis (-) group. Degenerative changes of the facet joints at both L4/L5 and L5/S were more severe in the unilateral spondylolysis (+) group than in the spondylolysis (-) group. Degenerative changes of the facet joints in patients with lumbar spondylolysis were more severe than those without spondylolysis.